The impact of case formulation meetings for teams. Issue 2 (7th March 2016) - Whitton, Clare; Small, Michelle; Lyon, Hayley; Barker, Lyndsie; Akiboh, Martina
Abstract : Purpose: – The purpose of this paper is to investigate the impact of psychological case formulation meetings for staff in a secure forensic learning disability and autism service. Design/methodology/approach: – In total, 89 of the attendees completed a questionnaire prior to the formulation meeting and then another questionnaire following attendance at a formulation meeting. Findings: – The results indicate that staff found these to be a helpful, informative and a positive experience professionally and personally. The results suggest that the formulation meetings developed staffs' psychological understanding about the patient and their problems, helped to increase their empathy towards the patient, increased consistency in the teams' views, and that the staff felt listened to. Research limitations/implications: – Psychological formulation meetings are established in the current service, and therefore this may be a contributing to factor to the lack of significant change found in some of the items. Therefore, it would be beneficial for future services to complete a service evaluation at a much earlier point of implementation, as this may impact the level of significance. Originality/value: – The findings of this service evaluation suggest that formulation is a beneficial and useful tool for teams and would be a helpful tool for psychologists to use in the clinical work with teams.